Inventing God's law: how the covenant code of the Bible used and revised the laws of Hammurabi - Wright, David P. (Oxford University Press, 2009)
David Wright argues that the so-called Covenant Collection of the Torah (Exodus 20:23-23:19) is chiefly the work of a single author, is the result of intellectual interaction with the author's sources & it may have had a politically ideological purpose, somewhat similar to that of the Laws of Hammurabi.